2019
DOI: 10.18632/oncotarget.26960
|View full text |Cite
|
Sign up to set email alerts
|

PI3K inhibition enhances the anti-tumor effect of eribulin in triple negative breast cancer

Abstract: Loss of the tumor suppressor phosphatase and tensin homolog (PTEN) is commonly observed in triple negative breast cancer (TNBC), leading to activation of the phosphoinositide 3-kinase (PI3K) signaling to promote tumor cell growth and chemotherapy resistance. In this study, we investigated whether adding a pan-PI3K inhibitor could improve the cytotoxic effect of eribulin, a non-taxane microtubule inhibitor, in TNBC patient-derived xenograft models (PDX) with loss of PTEN, and the underlying molecular mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 55 publications
3
10
0
Order By: Relevance
“…The discrepancy between our results and the in vitro evidence in Kurebayashi et al [ 16 ] could be attributed to the relatively small number of CTCs analyzed, the significant heterogeneity of CTCs as compared to cell lines, and the different methodologies employed that could possibly identify different CSC-like populations displaying distinct properties. On the other hand, our findings corroborate preclinical findings in BC, showing that eribulin resistance is promoted by the activation of the PI3K/AKT pathway [ 21 ], which holds a key role in maintaining the stemness of BC cells [ 22 ], and that the combination of eribulin with PI3K inhibition has synergistic antitumor effects by reducing the breast CSC population [ 30 ]. The role of CSCs in primary and acquired resistance to eribulin needs further investigation in BC patients, and analyses at the CTC level could be very informative in this regard.…”
Section: Discussionsupporting
confidence: 87%
“…The discrepancy between our results and the in vitro evidence in Kurebayashi et al [ 16 ] could be attributed to the relatively small number of CTCs analyzed, the significant heterogeneity of CTCs as compared to cell lines, and the different methodologies employed that could possibly identify different CSC-like populations displaying distinct properties. On the other hand, our findings corroborate preclinical findings in BC, showing that eribulin resistance is promoted by the activation of the PI3K/AKT pathway [ 21 ], which holds a key role in maintaining the stemness of BC cells [ 22 ], and that the combination of eribulin with PI3K inhibition has synergistic antitumor effects by reducing the breast CSC population [ 30 ]. The role of CSCs in primary and acquired resistance to eribulin needs further investigation in BC patients, and analyses at the CTC level could be very informative in this regard.…”
Section: Discussionsupporting
confidence: 87%
“…PDX models offer a unique resource for biomarker discovery. Several baseline biomarkers that were found to correlate with less responsiveness to BKM120 were reported previously in association with PI3K inhibitor resistance, for example upregulated RTK [ 26 , 27 ], EMT [ 28 , 29 ], and anti-apoptotic signaling [ 30 ]. However, other markers including PI3Kp85 regulatory subunit, NFKB pathway (IkappaB, RANKL), and intracellular signaling molecules including Caveolin, CBP, and KLF4 are also identified, which could represent potential novel resistance mechanisms.…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, the enriched biological pathways of the DEGs we selected included MET, mTOR signaling pathway and IL-3 mediated signaling pathway. Numerous studies had reported epithelial-to-mesenchymal transition (EMT) can be induced by receptor tyrosine kinases (RTKs) including c-Met, epithelial growth factorreceptors and IGF-1R, and EMT always promoted tumor progression, in development of carcinoma, RAF/ MEK/ERK1/2 axis, PI3k/Akt/mTOR pathways, and phosphorylation of β-catenin were play a critical role (39)(40)(41). Function analysis helps us better to understand the mechanism of TNBC and provides a guide for TNBC prevention and treatment; however, further laboratory and clinical researchers are required to verify this.…”
Section: Discussionmentioning
confidence: 99%